The optimal solution when planning to use workers as a labor force (Journal of Economic Research & Business Administration, 2017)
To enhance competition in the construction industry market productiveactivities of employees of the organization allows us to consider as akey factor as a strategic resource in achieving success. Currently, due to theefficient use of scarce resources, employees are often made with economicefficiency, through the use of that represents through the implementationof the organization’s goals and care workers, preferences, interests andneeds for razrabotkoj characterizing “efficiency” is used more and moreoften. Proper placement of the workforce to jobs in the organization inaccordance with the particular optimal assignment is the main purpose inplanning taken by employees as polimernoe use of human resources. Insome projects, the number of employees is governed by the adoption ordismissal of employees, Because, along with the adoption of the workforceand their dismissal is connected with additional costs.